(untitled) (Bangladesh Journal of Medicine, 2023)
Dengue and typhoid fever are different entities with overlapping signs and symptoms. The resemblance of symptoms makes clinical diagnosis and treatment difficult. Both are major health problems mainly during monsoon. If they are not diagnosed timely and treated, outcome can be fatal. We report 2 cases of dengue virus co-infection with typhoid fever during this outbreak of dengue. The aim of this report was to create awareness about this co-infection Bangladesh J Medicine 2023; 34(3): 239-240